2016
DOI: 10.1111/bju.13502
|View full text |Cite
|
Sign up to set email alerts
|

Robot‐assisted technique for Boari flap ureteric reimplantation: replicating the techniques of open surgery in robotics

Abstract: ObjectiveTo describe our robot-assisted Boari flap ureteric reimplantation (RA-BFUR) technique, Please see Video S1. MethodsThe RA-BFUR technique is based on the open surgical technique of € Ubelh€ or, and the experience includes 11 cases. ResultsExcellent results were achieved after a mean follow-up period of >12 months. ConclusionThe RA-BFUR technique could be considered a safe and effective method of ureteric reimplantation for long distal ureteric strictures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 5 publications
0
15
0
1
Order By: Relevance
“…On review of the literature we identified 17 studies ( Table 5 [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , [74] , [75] , [76] , [77] , [78] , [79] , [80] , [81] , [82] ) evaluating distal ureteric reconstructive surgery, with institutions presenting their experience using a number of differing techniques including uretero-ureterostomy and uretero-neocystostomy (often with adjunct procedures such as Boari flap formation or Psoas hitch).…”
Section: Robot-assisted Distal Ureteric Reconstructionmentioning
confidence: 99%
“…On review of the literature we identified 17 studies ( Table 5 [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , [74] , [75] , [76] , [77] , [78] , [79] , [80] , [81] , [82] ) evaluating distal ureteric reconstructive surgery, with institutions presenting their experience using a number of differing techniques including uretero-ureterostomy and uretero-neocystostomy (often with adjunct procedures such as Boari flap formation or Psoas hitch).…”
Section: Robot-assisted Distal Ureteric Reconstructionmentioning
confidence: 99%
“…thologies [5,6,13,[16][17][18]20,21,[25][26][27][28][29][30][31]. Additionally, in 2011, Yang et al [28] published their single institution series which included one patient with endometriosis and another with ureteral transection during a GYN procedure.…”
Section: Ral Distal Ureteral Reconstructionmentioning
confidence: 99%
“…The authors discussed a novel technique for ureteral stent placement using a Council tip Foley catheter via the bladder and retrograde insertion into the ureter by the existing cystotomy. In 2016, Stolzenburg et al [29] reported the largest series of RAL reimplantation with BF in 11 patients with benign ureteral strictures. The authors reported success in all patients at 15 months of follow-up.…”
Section: Ral Distal Ureteral Reconstructionmentioning
confidence: 99%
“…Meanwhile, operative time and complication rates were similar. Ureteric reimplantation for long defects of the ureter has also safely and effectively replicated the steps of open surgery in the intracorporeal environment with the use of a Boari flap or ileal segment interposition, in small case series [9,10]. There is some debate with regard to the best technique of ureteric reimplantation.…”
Section: Evidence Acquisitionmentioning
confidence: 99%